2019
DOI: 10.1002/prep.201800291
|View full text |Cite
|
Sign up to set email alerts
|

A Thermal Study of a Simple Al−CuO Pyrotechnic Crackle Composition

Abstract: The reaction temperature in ignited samples of a novel, chemically simple pyrotechnic crackle composition was monitored at 1 ms intervals by means of a small embedded thermocouple. Analysis of the results reveals that an exothermic reaction is detectable at temperatures as low as 500 K. The reaction is found to progress in at least three – and probably four – steps that correlate well with similar findings from the study of nanocomposites of the same composition. The first two steps are shown to be associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…As a hot research topic in recent years, nanothermites have found uses in a multitude of applications. These include their uses as detonation initiators [ 6 ], pyrotechnics [ 7 ], aerospace devices [ 8 , 9 ], airbag ignition materials [ 10 ], and in biomedical applications [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a hot research topic in recent years, nanothermites have found uses in a multitude of applications. These include their uses as detonation initiators [ 6 ], pyrotechnics [ 7 ], aerospace devices [ 8 , 9 ], airbag ignition materials [ 10 ], and in biomedical applications [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%